KONSEP TADRIJ DAN TAKRIR IBNU KHALDUN SEBAGAI METODE PEMBELAJARAN - Nur Kahfi; Fathi Hidayah; Muhammad Endy Fadlullah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
This study aims to describe the tadrij and takrir methods found in the Muqaddimah by Ibn Khaldun. The research data were obtained through documentation techniques, where the primary data source was the Muqaddimah of Ibn Khaldun. Furthermore, the data were analyzed using content analysis techniques to get conclusions. The conclusion in this study is about the tadrij method is a teacher must gradually, when the teacher gives material, he must start from the easy things first and gradually move on to difficult lessons, repeat the subject matter up to three times and avoid violence at teaching time from understanding the simplest and easiest problems, then increasing slowly to understand and mastering things that are rather complex, then more complex, very complex and so on. Ibn Khaldun's thoughts about the takrir method or the repetition method is the repetition was carried out three times, this repetition aims so that the knowledge that has been previously understood is not forgotten and each repetition is given a higher level of material than before that the level of understanding will increase.